2022
DOI: 10.1007/s10570-022-04854-6
|View full text |Cite
|
Sign up to set email alerts
|

Highly compressible hydrogel reinforced with cellulose nanocrystals for ultrasound scanning via microwave-assisted synthesis

Abstract: In this study, a rapid fabrication method was developed to prepare hydrogel structures with high mechanical strength and low attenuation coe cient for ultrasound scanning. Poly acrylic acid (PAA) hydrogel was rst prepared via a free radical polymerization approach. To shorten the process time (~ 30 minutes in water bath), microwave heating was applied to facilitate the reaction and reduce the reaction time down to 80 seconds. The produced hydrogels showed excellent elasticity but had a low compressive strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Yet, we found that adding 0.5 wt % CNC to the hydrogel without LM did not cause a meaningful change in mechanical properties (Figure S15), even though there are literature examples in which CNC can toughen the PAA gels. 54,55 The lack of meaningful change might be due to the lower aspect ratio of CNCs (L/D around 9, according to TEM images) used in this work. We selected CNCs with a lower aspect ratio to avoid aggregation and improve coating the LM.…”
Section: Resultsmentioning
confidence: 97%
“…Yet, we found that adding 0.5 wt % CNC to the hydrogel without LM did not cause a meaningful change in mechanical properties (Figure S15), even though there are literature examples in which CNC can toughen the PAA gels. 54,55 The lack of meaningful change might be due to the lower aspect ratio of CNCs (L/D around 9, according to TEM images) used in this work. We selected CNCs with a lower aspect ratio to avoid aggregation and improve coating the LM.…”
Section: Resultsmentioning
confidence: 97%
“…Pi et al, prepared CNC/Mxene PVA/PAAM hydrogels with desirable strain-sensitive conductivity and good thermal resistivity [33]. Cheng et al used microwave incorporation to prepare PAA/CNC hydrogels with good biocompatibility and high transmission to ultrasound [34]. Peng et al, cross-linked hydrogels with a high swelling rate using quaternized membranous cellulose nanocrystals (Q-TCNCs), carboxymethylcellulose (CMC), and epichlorohydrin (EPI), and their mechanical properties and swelling rate could be controlled by adjusting the Q-TCNCs content [35].…”
Section: Introductionmentioning
confidence: 99%